2014
DOI: 10.4067/s0717-95022014000200033
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Binge-Like Ethanol Administration During Adolescence cause Decreased C-Fos Immunoreactivity in Amygdala and Arcuate Nucleus in Adult Sprague-Dawley Rats

Abstract: SUMMARY:Binge alcohol drinking during adolescence has been associated with neurotoxicity and increased risk for the development of alcohol use disorders. There is evidence that acute and chronic ethanol administration alters c-fos expression, an indirect index of cellular activity, in different brain regions in adult rats. We evaluate here if a binge-like pattern of ethanol exposure during adolescence has a relevant impact on basal and/or ethanol-stimulated regional c-fos activity during adulthood. For that ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In contrast, in our study, the nonobserved change in c‐Fos expression in adult mice exposed to a CIA could be the consequence of the activation of the genes associated with protective mechanisms that prevent cells from oxidative damage (Lacaille et al., ). Then, the following observed decrease in c‐Fos hippocampal expression in adulthood after CIA may reflect some neural adaptations in our study, as suggested by Lerma‐Cabrera and colleagues (). Indeed, the authors observed a similar decrease in adult rats exposed to CIA in adolescence in other structures such as the hypothalamus and the amygdala.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, in our study, the nonobserved change in c‐Fos expression in adult mice exposed to a CIA could be the consequence of the activation of the genes associated with protective mechanisms that prevent cells from oxidative damage (Lacaille et al., ). Then, the following observed decrease in c‐Fos hippocampal expression in adulthood after CIA may reflect some neural adaptations in our study, as suggested by Lerma‐Cabrera and colleagues (). Indeed, the authors observed a similar decrease in adult rats exposed to CIA in adolescence in other structures such as the hypothalamus and the amygdala.…”
Section: Discussionsupporting
confidence: 79%